PERANCANGAN APLIKASI BUKU TAMU ANTI GRATIFIKASI BERBASIS WEBSITE PADA KEMENTERIAN PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI - Muhammad Yusuf Danan Risdianto (2023)
Human life is improved by technology, which serves as a vessel. However, agencies such as the Ministry of Education, Culture, Research and Technology have not fully utilized technology. The Ministry of Education, Culture, Research and Technology is still collecting data and recording guest books manually using paper forms, which slows down the work process, there are no records of gratuities and is not effective in bookkeeping. In addition, the use of manual systems carries significant risks of data corruption, redundancy and loss. Therefore the author created an information system for recording guest books to help the Ministry of Education, Culture, Research and Technology reduce risk and make it easier to record and collect guest book data with gratuity reports. The author uses PIECES problem analysis, UML visual modeling, and the waterfall system design method. MySQL database and PHP programming language are used in making this system. This research produces a web that can handle and record data properly in real time and with up-to-date information.